School, racialization and intercultural education - Claudia María Rodríguez Castrillón; Sandra Milena Robayo Noreña; Sandra Elizabeth Colorado Rendón; Karol Belisa Ospina Diaz (University of Bologna, 2024)
Girls and boys are immersed in social discussions to validate their agency. There are imaginaries, representations and narratives around childhood that designate the place of girls and boys in different cultures. The issue of intersections in childhood requires expanding debates and problematizing structural issues of the life course in relation to gender, age, ethnicity and social class, to account for their impact on girls and boys. At the same time, displace imaginaries from colonialism and mobilize a social consciousness that recognizes diversity not as a dichotomy between us and the others, but as the protagonism of dignity. This article explores, based on documentary research, the conditions under which boys and girls from different regions of Colombia access education, in the midst of situations such as migration, ethnicity, displacement and multiple forms of family poverty. It is concluded, therefore, that racialized girls and boys are at greater social disadvantage, given their socio-historical living conditions.